Epidemiology of Genital Chlamydial Infection in China in 2019 - Xiao-Li Yue; Xiang-Dong Gong; Jing Li; Jia-Hui Zhang; Heng Gu (Wolters Kluwer Health, 2020)
Abstract. Objective:. Genital chlamydial infection is a globally common sexually transmitted infection caused by Chlamydia trachomatis. This study aimed to describe the epidemiological characteristics of the disease reported in China in 2019. Methods:. Genital chlamydial infection cases were identified in 105 national sexually transmitted disease surveillance sites from the National Notifiable Infectious Disease Reporting System, which covers 31 provinces, autonomous regions, and municipalities in Chinese mainland. Data were collected and used to calculate the overall incidence, and the incidences per surveillance site, province, sex, and age group. Results:. In 2019, there were 50,874 new cases of genital chlamydial infection reported in China, corresponding to an incidence of 55.32 cases per 100,000 population, and comprising a 9.98% increase from 2018 (50.30 cases per 100,000 population). The highest incidences of genital chlamydial infection occurred in Zhejiang, Guangdong province, Guangxi autonomous region, and Hainan province (average 137.49-233.37 cases per 100,000 population). The incidence of genital chlamydial infection was much higher in females than males, with a female-to-male ratio of 3.09 (84.55 per 100,000 population vs 27.35 per 100,000 population). The highest incidence of genital chlamydial infection was reported in the 20-24-year age group (184.70 cases per 100,000 population), followed by the 25-29-year age group (180.79 cases per 100,000) and 30-34-year age group (151.53 cases per 100,000 population). The highest proportion (68.30%) of genital chlamydial infection was reported from general hospitals, followed by maternal and child health hospitals (25.59%). Conclusion:. The incidence rate of genital chlamydial infection in 2019 has an increase trend from 2018 and be a common sexually transmitted infection in China. The incidence is much higher in females than in males. Sexually active young adults are the highest risk population. There is substantial geographic diversity in incidence, with the highest incidence occurring in the southeast coastal areas with a developed economy. Epidemic of genital chlamydial infection in China should be concerned, and its surveillance needs to be improved.